Hyundai's dynamics of styling-driven capability development: a historical analysis of the 1970s-1990s. (2015) - Choi, Eugene
Toyota-ism has been the supreme straightedge of indicating technical advancement in automotive manufacturing in the absolute majority of the past scholarly investigation on the Japanese and South Korean automotive industries. Their key interests were single-mindedly placed upon engineering Kaizen. This paper intends to present an introductory study on Hyundai's evolution of capability development in automotive styling. This historical analysis examines the enduring foundation of styling-driven product strategy in Hyundai's past four decades with many vicissitudes. The impact of styling capability becomes unprecedentedly significant along with the levelling of engineering capability. Delivering a new compound of perceived qualities, derived from Imiteki Kachi (semantic value) for global customers would be vital. Now on the verge of facing an epoch of eco-friendly automobiles, it would be even more essential to reconsider the strategic significance of styling and its reciprocal relation with technological furtherance in the upcoming evolution of the global automotive industry henceforth.